The structural linguistics patterns of the written component of Malaysian University English Test (MUET) - Sarjit Singh, Manvender Kaur; Shamsudin, Sarimah; Isam, Hishamuddin; Surjit Singh, Naginder Kaur; Pertap Singh, Gurmit Singh; Kanestion, Anita (2016)
The need to focus future education according to the actual needs of the learners can be realized by conducting a well-placed research within the prospective requirements of its context. However, evaluating and accessing the actual linguistics needs of learners is undeniably a challenging undertaking. This paper presents steps taken to conduct a descriptive and a corpus-based study. It explored the written essays produced by ESL learners.The areas of investigation involved examining the strategies used by the language learners while preparing the essays, the frequency of part-of-speech (POS) used in the essays and sentence level syntactical analysis of the most frequently used POS.The methodology applied is fundamental as it tends to investigate the linguistic constituents in the compiled corpus. Computer-based syntactical studies are limited as it requires hard work, long hours and complex analytic method of describing the findings. In contrast, this article demonstrated an uncomplicated method of analysis and also encourages the use of existing part-of speech (POS) tagging software available online.The findings show that the students are using mainly the past participle form of the lexical verb (VVN) when preparing the written essays.As recommendations for future research, this paper proposes structural linguistics investigations such as frequency analyses, sentence level syntactical analyses (SLSA), examining the distributional patterns of sentence level linguistic structural patterns and subject-verb agreement analyses reflecting the writers’ knowledge of applying their grammatical linguistics knowledge into their written output be conducted within various contexts where language is used.